Prototipe Papan Partikel Tahan Air Berbahan Baku Limbah Kayu Sebagai Material Partisi Ruang: Waterproof Particleboard Prototype Made from Wood Waste as Room Partition Material - Mahdi Santoso; Noor Hamidah; Dwi Anung Nindito; Adhitya Gantin Ranu; Ilham Qodir Siregar; Jon Riston Saragih; Wahyunita; Bahrul Yoga (JURNAL HUTAN TROPIKA, 2026)
This study aims to evaluate the effects of ammonium dihydrogen phosphate (ADP) additive content, particle type, and layering technique on bonding properties of particleboard of white meranti (Shorea spp.) sawdust. The first stage examined the influence of ADP addition at concentrations of 0%, 5%, and 10% on the bonding properties of particleboard. The results indicated that all physical properties satisfied the requirements of SNI 03-2105:2006 and FAO:1966 standards; however, most mechanical properties did not meet the SNI standard, presumably due to the interference of ADP with adhesive bonding between particles. The second stage analyzed the effects of particle type and layering technique by increasing the polyurethane adhesive content to 20% without additive addition. This treatment significantly improved the mechanical properties, particularly for sawdust-based particleboard with a three-layer structure, enabling compliance with SNI 03-2105:2006 requirements. The third stage produced a particleboard prototype as an interior partition module, which exhibited physical and mechanical properties that met the applicable standards. Particleboard manufactured from white meranti sawdust bonded with 20% polyurethane adhesive is suitable for interior non-structural applications such as furniture and space partitions